Isolation and Biochemical Test of Microalgae in The Floating Net Cage Area of The Koto Panjang Reservoir, Kampar Regency, Riau Province - Mei Kristiyani Simanjuntak; Kamaruddin Eddiwan; Budijono Budijono (Berkala Perikanan Terubuk, 2023)
Identification, isolation, and analysis of the biochemical content contained in microalgae. This research was conducted from June to September 2022. The survey method was used, and the data obtained were analyzed descriptively and quantitatively. Primary data collection was carried out by observing in the field and analyzing in the laboratory, while secondary data was obtained from books, journals, and the internet. The identification results of microalgae from the waters of the Koto Panjang hydropower reservoir found as many as 30 species consisting of 3 classes. The type of microalgae that has the two highest abundances is the type of Chlorococcum sp. and Nitzschia sp. From the results of the microalgae isolation culture from the Koto Panjanhg Hydropower Reservoir in the Laboratory period, harvesting was carried out in the peak phase, namely for Chlorococcum sp. on day 9 (with a dry weight of 0.57 g) and Nitzschia sp. on the 8th day (with a dry weight of 0.42 g). While the proximate content of the microalgae type Chlorococcum sp. namely: carbohydrates 6.75%; protein 10.7742%; fat 19.75%; meanwhile, the proximate content of Nitzschia sp. namely: carbohydrates 10.8%; protein 10.7742%; fat 0.25%. Then the phytochemical content obtained was alkaloid (only found in Chlorococcum sp. Furthermore, saponins, steroids, glycosides, and flavonoids were found in the two microalgae isolates, while the triterpenoid content was not found in the two microalgae isolates.